Advanced Strategies for Enhancing Smart Farming Through Innovative IoT Techniques - Mathur, Garima; Tripathi, Vaibhav (International Journal of Computer Sciences and Engineering, 2024)
Smart farming is a significant application of the Internet of Things (IoT). It minimizes water, fertilizer, and crop yield waste. Sustainable development is confronted with two of the world`s most pressing problems: the food shortage and the rapid increase in population. Utilizing the infrastructure to use modern technologies like the Internet of Things, big data, and the cloud, smart farming has evolved into a systematic method of managing and monitoring sustainable agriculture. Data optimization is necessary for IoT-cloud systems due to the large amounts of data involved, both organized and unstructured. IoT-based smart farming improves the farming system by monitoring fields of crops. The IoTs in agriculture enable farmers to save time and reduce the consumption of resources such as water. The main aim of this review article is to offer a comprehensive analysis from a social and technological perspective. Important application domains, IoT architecture, and various problems are covered in this paper. In addition, the paper explores the available literature and shows their impact on many parts of the Internet of Things.